Malaysia's cocoa beans decline: a prognosis - Mohamed Arshad, Fatimah; Ibragimov, Abdulla (Zes Rokman Resources, 2015)
The Malaysian cocoa beans has gone through a complete cycle of production from a stellar performance in the 1990s to almost extinct in 2014. The production reached 400,000 tonnes during its heydays to a mere 3,000 tonnes in 2013, indicating an “overshoot” and later “collapse” behavior. This behavior invites questions such as: (i) What caused the overshoot and decline in production? and (ii) Is this an irreversible trend? This study attempts to answer these questions. The push factors that led to the abandonment of cocoa area are pest and diseases problem, unstable price, low productivity and hence return. The pull factors include: better return from oil palm farming and other non-cocoa enterprises. The intervening factors are plenty such as limited institutional supports to farmers, farm constraints and structural setback in the cocoa industry. In view of the complexity of the problem, a system dynamics methodology is used to capture the feedback relationships between variables that were responsible in shaping the production trends. A simulation is carried out on the impact of productivity enhancement and innovation in farm supply chain on the trends of cocoa production in the future.